Antibody-Mediated Clearance of Amyloid-β Peptide from Cerebral Amyloid Angiopathy Revealed by Quantitative In Vivo Imaging - Prada, Claudia M. (J Neurosci, 2007)
Cerebral amyloid angiopathy (CAA) is the accumulation of amyloid-β peptide (Aβ) in the vessel wall of arteries in the brain. Because CAA is commonly associated with Alzheimer's disease (AD), characterized by parenchymal deposition of the same peptide in the form of senile plaques, there is considerable interest in the relationship of the two deposits in generating human disease. The study of CAA is of particular importance for immunotherapeutic approaches to AD, because reports of anti-Aβ immunotherapy in mice and humans have suggested that, whereas CAA appeared resistant to clearance, its response to this treatment promoted potential adverse effects, including meningoencephalitis. We used multiphoton microscopy and longitudinal imaging to monitor CAA in a mouse model of amyloid deposition to evaluate the effects of anti-Aβ passive immunotherapy. We found detectable clearance of CAA deposits within 1 week after a single administration of antibody directly to the brain, an effect that was short-lived. Chronic administration of antibody over 2 weeks led to more robust clearance without evidence of hemorrhage or other destructive changes. We found that the progressive clearance of Aβ from vessels follows distinct kinetics from what has been previously reported for clearance of plaques (parenchymal deposits of Aβ). This quantitative in vivo imaging approach directly demonstrates that CAA in a transgenic mouse model can be cleared with an optimized immunotherapy.